Spaces of trust and mistrust : Congolese refugees, institutions and protection in Kampala, Uganda - Lyytinen, E; Lyytinen Eveliina (2013)
The spatiality of refugee protection has been a key issue for humanitarian practitioners and policy-makers, and it has become of increasing concern in academic studies. This study interrogates the policy and practice-oriented concept of ‘protection space’ in regard to the experiences of the Congolese refugees in the city of Kampala, Uganda. My analysis of ‘protection space’ uses the geographical concepts of the ‘right to the city’ and ‘sense of place’ to emphasise the physical, imagined, lived and relational understandings of urban space. I also investigate the conceptual links between ‘protection’, ‘space’ and ‘trust’. I apply a qualitative case-study approach in this study and collected primary data from individual Congolese refugees, refugee communities and officers of the protection institutions. The data-collection methods included a combination of semi-structured interviews, observation and focus group discussions, supported by visual methods. I rely on aspects of discourse analysis to analyse my textual and visual data. I conclude that the Congolese refugees informing this study conceptualised ‘protection’ not only legally, physically and relationally, but also spiritually. The geographical levels of protection and insecurity that refugees experienced varied: their ‘sense of place’ in relation to the city of exile depended on their micro-, meso-, and macro-scale experiences and perceptions of protection. Given the prevalence of generalised and particularised social mistrust and institutional mistrust – two matters that were intertwined in refugees’ discourses of their everyday urban life – it is concluded that the distinction between protection and insecurity was at times unclear. Refugees, however, found a sense of protection from various ‘communities of trust’, even though their community life was also characterised by struggles over their ‘right to the city’ and inter-community mistrust.